Metodologias de aplicação de sulfonamida heterocíclica no controle de Meloidogyne javanica e Pratylenchus brachyurus em soja - Oriani, Eduardo Elias [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Problems with nematodes have been increasing on soybeans fields. Programs for nematode population reduction are essential to reduce yield losses. Three application methodologies, using the novel sulfonamide nematicide, were tested to control M. javanica e P. brachyurus in soybean: 1) furrow application at sowing planting 2) broadcast application in the total area 5 days before planting, 3) furrow application at sowing and an additional total area application 20 days after emergence (DAE). Evaluations consisted in: i) number of plants per linear meter (14 DAE); ii) plants height and fresh weight of shoots (45 and 90 DAE); iii) nematode population of different developmental stages (eggs, juveniles and adults) in the roots (45 and 90 DAE); iv) gall index (45 and 90 DAE); v) yield. Among tested methodologies, sulfonamide nematicide furrow application at sowing presented M. javanica population reduction 45 DAE with 1.500 g a.i/ha and with 2.000 g a.i/ha was detected population reduction 90 DAE. This methodology did not reduce P. brachyurus population in any of the doses tested. The second methodology, with application in the total area 5 days before planting, reduced M. javanica population with 500 and 1.500 g a.i/ha 90 DAE. This methodology also reduced P. brachyurus with 1.500 g a.i/ha 45 DAE. The third methodology, sulfonamide nematicide furrow application at sowing (150 g a.i/ha) and an additional total area application 20 DAE (750 g a.i/ha) significantly reduced M. javanica population until 45 DAE and showed gall index reduction until 90 DAE. This methodology also did not have any effect on P. brachyurus population in any of the doses tested. In all methodologies tested the sulfonamide did not show negative crop response, did not increase the plant height, fresh weight and yield

Os problemas com nematoides aumentaram significativamente nas áreas de cultivo de soja e práticas de redução populacional são fundamentais para minimizar as perdas na produtividade. Três metodologias de aplicação, utilizando a nova sulfonamida nematicida, para controle do M. javanica e P. brachyurus em soja foram avaliadas: 1) aplicação no sulco de plantio sobre as sementes, 2) aplicação em área total 5 dias antes do plantio, 3) aplicação no sulco de plantio sobre as sementes, e mais uma aplicação complementar 20 dias após a emergência (DAE) em área total. Foram avaliados: i) número de plantas por metro linear (14 DAE); ii) altura das plantas e massa fresca da parte aérea (45 e 90 DAE); iii) população de diferentes estádios de desenvolvimento de nematoide (ovos, juvenis e adultos) nas raízes (45 e 90 DAE); iv) índice de galhas (45 e 90 DAE); v) produtividade. Dentre as metodologias testadas, a aplicação da sulfonamida nematicida aplicada no sulco de plantio sobre as sementes apresentou redução populacional de M. javanica aos 45 DAE na dose de 1.500 g i.a/ha e na dose de 2.000 g i.a/ha foi detectada redução populacional aos 90 DAE. Essa metodologia não mostrou efeito sobre P. brachyurus nas doses testadas. A segunda metodologia, com aplicação da sulfonamida, em área total 5 dias antes do plantio, reduziu a população de M. javanica aos 90 DAE nas doses de 500 e 1.500 g i.a/ha. Essa metodologia também reduziu a população de P. brachyurus aos 45 DAE na dose de 1.500 g i.a/ha. A terceira metodologia, com aplicação da sulfonamida nematicida no sulco de plantio (150 g i.a /ha) e mais uma aplicação complementar em área total 20 DAE (750 g i.a /ha) reduziu significativamente a população de M. javanica até 45 DAE e reduziu as galhas até 90 DAE. Essa metodologia não...
Keywords: Soja - Doenças e pragas - Controle; Defensivos vegetais; Nematoda em plantas; Produtos químicos agrícolas; Sulfonamidas; Agricultural pests Control